2012
DOI: 10.1002/elan.201100594
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Matrine Using a New Voltammetric Sensor Based on L‐Cysteine/Graphene Oxide‐Chitosan Composite Film Modified Electrode

Abstract: A new voltammetric sensor for matrine was fabricated via the polymerization of l-cysteine on graphene oxide, which served as templates. The fabricated electrode can improve the oxidation of matrine intensively, and enable the determination of matrine in the range from 4 10 À6 to 1 10 À4 mol L À1 , with a detection limit of 2 10 À6 mol L À1. The oxidation process of matrine was studied and some dynamic parameters were calculated using various electrochemical techniques. This present sensor displayed good stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…It was found that the same electrons and protons are consumed in the electrode reaction as indicated by the slope of the regression equation. Therefore, the oxidation mechanism for matrine can be written as shown in Figure 4 , which is in accordance with the report [ 23 , 66 ]. Besides, the i pa varies very little in the range of 7.0–7.5, so the solution pH of 7.5 was chosen in the following experiments, which is close to the human physiological pH.…”
Section: Resultssupporting
confidence: 83%
“…It was found that the same electrons and protons are consumed in the electrode reaction as indicated by the slope of the regression equation. Therefore, the oxidation mechanism for matrine can be written as shown in Figure 4 , which is in accordance with the report [ 23 , 66 ]. Besides, the i pa varies very little in the range of 7.0–7.5, so the solution pH of 7.5 was chosen in the following experiments, which is close to the human physiological pH.…”
Section: Resultssupporting
confidence: 83%
“…Electrodes modified with a graphene based electrocatalyst have been used for detecting various inorganic or organic electroactive compounds, such as hydrogen peroxide (H 2 O 2 ), b-nicotinamide adenine dinucleotide (NADH), acetaminophen (APAP), dopamine (DA), ascorbic acid (AA), uric acid (UA) and matrine. 219,221,[226][227][228][229][230][231][232][233][234][235][236][237] A typical electrocatalyst for this purpose is rGO and the simplest sensing electrode is an rGO modified glassy carbon electrode (rGO-GC). The rGO-GC electrode has been explored for sensing DNA, H 2 O 2 , NADH, APAP, DA, UA or AA.…”
Section: Inherent Catalystsmentioning
confidence: 99%
“…L-Cysteine functionalized GO (LC-GO) can enhance the oxidation of matrine, and a LC-GO-GC electrode can detect matrine in a concentration range of 4 mmol L À1 to 0.1 mmol L À1 . 236 A variety of electrochemical sensors based on the graphene composite catalysts containing metals have also been developed. Titanium nitride/nitrogen-doped graphene (TiN/NG) provided a reliable platform for the determination of NADH with a linear dynamic range of 2.0-687 mM at a working potential of 0.1 V (vs. Ag/AgCl).…”
Section: Inherent Catalystsmentioning
confidence: 99%
“…The electrochemical effective surface areas of bare GCE and PIL-EG/GCE were calculated by the slope of the plot of Q versus t 1/2 obtained by chronocoulometry using 1mmol/L K 3 [Fe(CN) 6 ] as model complex (the diffusion coefficient D of K 3 [Fe(CN) 6 ] is 7.6×10 -6 cm 2 /s) 30 based on the equation of Q = 2nFAc(Dt) 1/2 /π 1/2 + Q dl + Q ads 31 , where A is the electrode surface area, n is the number of electrons transferred, F is the Faraday constant, c is the concentration of substrate, D is the diffusion coefficient, Q dl is double layer charge which could be eliminated by background subtraction and Q ads is the Faradic charge. In this study, the corresponding A of bare GCE and the modified electrode were obtained to be 0.0397 and 0.2417 cm 2 .…”
Section: Calculation Of Electrochemical Effective Surface and Saturatmentioning
confidence: 99%